International Continence Society (ICS) report on the terminology for sexual health in men with lower urinary tract (LUT) and pelvic floor (PF) dysfunction. Issue 1 (6th January 2022) - Kocjancic, Ervin; Chung, Eric; Garzon, Joaquin Alvarez; Haylen, Bernard; Iacovelli, Valerio; Jaunarena, Jorge; Locke, Jennifer; Millman, Alexandra; Nahon, Irmina; Ohlander, Samuel; Pang, Ran; Plata, Mauricio; et al.
Abstract: Introduction: The terminology for sexual health in men with lower urinary tract (LUT) and pelvic floor (PF) dysfunction has not been defined and organized into a clinically based consensus terminology report. The aim of this terminology report is to provide a definitional document within this context that will assist clinical practice and research. Methods: This report combines the input of the members of sexual health in men with LUT and PF Dysfunction working group of the International Continence Society (ICS), assisted at intervals by external referees. Appropriate core clinical categories and a sub‐classification were developed to give coding to definitions. An extensive process of 18 rounds of internal and external review was involved to exhaustively examine each definition, with decision‐making by collective opinion (consensus). The Committee retained evidence‐based definitions, identified gaps, and updated or discarded outdated definitions. Expert opinions were used when evidence was insufficient or absent. Results: A terminology report for sexual health in men with LUT and PF dysfunction, encompassing 198 (178 NEW ) separate definitions, has been developed. It is clinically based with the most common diagnoses defined. Clarity and user‐friendliness have been key aims to make it interpretable by practitioners and trainees in all the different speciality groups involved. Conservative and surgical managements are major additions and appropriate figures have been included to supplement and clarify the text. Emerging concepts and measurements, in use in the literature and offering further research potential, but requiring further validation, have been included as an appendix. Interval (5–10 years) review is anticipated to keep the document updated. Conclusion: A consensus‐based terminology report for sexual health in men with LUT and PF dysfunction has been produced to aid clinical practice and research. The definitions that have been adopted are those that are most strongly supported by the literature at this time or are considered clinical principles or consensus of experts' opinions.